INTERNALISASI SIKAP TOLERANSI ANTARETNIK MELALUI MODEL PEMBELAJARAN RADEC DI SEKOLAH DASAR - Sulistiani, Vivi Ayu; Sari, Sri Yulia; Saputra, Donal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The management of ethnic diversity in elementary schools remains a critical challenge in Indonesia's education system. This study addresses the issue of low interethnic tolerance among fourth-grade students who tend to segregate based on tribal backgrounds. To overcome this, the RADEC (Read, Answer, Discuss, Explain, Create) learning model was implemented as an intervention. This Classroom Action Research (CAR) was conducted over two cycles involving 21 students at a public elementary school in Tebo Regency. Data were gathered through observation of teacher activities and questionnaires measuring tolerance attitudes. The findings revealed a significant transformation: whereas 57.14% of students were initially categorized as having low tolerance, the final cycle saw 100% of students achieving high and very high tolerance categories. The RADEC model proved effective not only in improving cognitive understanding but also in fostering social collaboration through structured interaction phases.